Byron - the years of fame - Quennell, Peter (London Penguin Books, 2001)
Contents Include: The Traveller Returns Literary Friendships Social Triumphs The Year of the Waltz Miss Milbank Cheltenham Lady Oxford Madame de Stael Lady Frances Mary Chaworth Reappears Thoughts of Marriage First Visit to Seaham Byron at Six Mile Bottom Byron Leaves England Keywords: Six Mile Bottom Literary Friendships Traveller Returns Lady Frances Madame De Stael Milbank Cheltenham Waltz Triumphs Oxford Marriage England.